2020
DOI: 10.1002/ps.6124
|View full text |Cite
|
Sign up to set email alerts
|

Immunotranscriptome analysis of Plutella xylostella reveals differences in innate immune responses to low‐ and high‐virulence Beauveria bassiana strain challenges

Abstract: BACKGROUND Entomopathogenic fungi have developed multiple strategies to overcome the immune defenses of their target insects, whereas insect pests have devised various defense mechanisms to combat fungal infection. However, differences in the molecular mechanisms of the innate immune defense strategies of insects upon infection with different fungal strains from the same species have not been reported. RESULTS Two Beauveria bassiana strains were obtained that significantly varied in their pathogenicity but wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
0
11
1
Order By: Relevance
“…However, our results were not completely consistent with the results observed in the whitefly ( Bemisia tabaci )‐ B. bassiana interaction system, in which the relative abundances of most metabolism‐related genes displayed a trend of downregulation in the whitefly infected by B. bassiana when compared with the control 46 . This result suggested that the interaction mechanisms in different insect‐fungus systems were not conserved, which is consistent with the findings of recent studies focused on host‐pathogen interactions using models of the same host insect‐different fungi or different host insects‐same fungi 18,47 …”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…However, our results were not completely consistent with the results observed in the whitefly ( Bemisia tabaci )‐ B. bassiana interaction system, in which the relative abundances of most metabolism‐related genes displayed a trend of downregulation in the whitefly infected by B. bassiana when compared with the control 46 . This result suggested that the interaction mechanisms in different insect‐fungus systems were not conserved, which is consistent with the findings of recent studies focused on host‐pathogen interactions using models of the same host insect‐different fungi or different host insects‐same fungi 18,47 …”
Section: Discussioncontrasting
confidence: 73%
“…46 This result suggested that the interaction mechanisms in different insect-fungus systems were not conserved, which is consistent with the findings of recent studies focused on host-pathogen interactions using models of the same host insect-different fungi or different host insects-same fungi. 18,47 For fungal DEGs involved in BPH-Ma456 interaction, most of the upregulated genes belonged to the functional category of ribosome biogenesis, suggesting that the fungal protein anabolism tended to be vigorous during the course of infection. It is generally known that entomopathogenic fungi produce many kinds of cuticle-degrading enzymes to facilitate penetration through the outmost cuticular barrier of the host, such as proteases, chitinases and lipolytic enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…B. bassiana strains, Bb6, Bb9, Bb11, and Bb20 were used in this study; they were stored at the Research Center for Entomogenous Fungi of Anhui Agricultural University, Anhui Province, China (Wang et al. , 2021c). All strains were stored in liquid nitrogen and transferred to Sabouraud dextrose agar with yeast extract (SDAY) in the dark at 25 °C for activation before use.…”
Section: Methodsmentioning
confidence: 99%
“…To silence different core components of the RNAi machinery in S . vaninii , dsRNAs targeting RNA-dependent RNA polymerase s, dicers , and argonautes were synthesized with T7 RNA polymerase (T7 RiboMAX Express RNAi system kit, Promega, Madison, WI, USA) based on established protocols ( 44 ). Briefly, ~300 bp DNA fragments, introduced at both the 5′ and 3′ ends with the T7 promoter sequence, were produced via PCR (PCR) from cDNA.…”
Section: Methodsmentioning
confidence: 99%